Fluorescently labeled risedronate and related analogues: "magic linker" synthesis. - Kashemirov, B; Bala, J; Chen, X; Ebetino, F; Xia, Z; Russell, R; Coxon, F; Roelofs, A; Rogers, M; McKenna, C (2008)
We report synthesis of the first fluorescently labeled conjugates of risedronate (1), using an epoxide linker strategy enabling conjugation of 1 via its pyridyl nitrogen with the label (carboxyfluorescein). Unlike prior approaches to create fluorescent bisphosphonate probes, the new linking chemistry did not abolish the ability to inhibit protein prenylation in vitro, while significantly retaining hydroxyapatite affinity. The utility of a fluorescent 1 conjugate in visualizing osteoclast resorption in vitro was demonstrated.